The scope and limits of machine translation - Cieślak Magdalena (elingUP: Revista Eletrónica de Linguística dos Estudantes da Universidade do Porto, 2017)
Even though no one is capable of providing an exact list of rules that would allow to arrive at a perfect translation, there are some procedures and methods, knowledge of which may facilitate translators' work. In order to have an idea about translation itself and be able to produce texts in various languages, one should get familiar with the process and theory of translation. The awareness of both notions may provide necessary advice and clues. What is more, it may be beneficiary for the translators' competence: increasing the quality of their work; enabling them to deliver the translation according to the rules, style, and grammar of the TL; allowing for quick, accurate, clear and naturally sounding translation.